Institutional governance and human development: Organizational justice and work commitment in advancing local and global SDGs - Sartono; Muhammad Yusuf; Liwaul; La Ode Muhammad Elwan; Taufik; Hasddin (Masyarakat, Kebudayaan dan Politik, 2026)
The Sustainable Development Goals (SDGs) emphasize institutional governance and human development as key components. This study examines how organizational justice, organizational politics, and work commitment influence human development in Kendari City, specifically focusing on sustainability and SDGs. A combination of quantitative and qualitative methods was used to answer the research questions of this study. Quantitative analysis was conducted using data from a government employee survey and human development indicators (HDI, per capita income, unemployment rate, and GDP growth), while qualitative analysis relied on in-depth interviews and document reviews to identify organizational and cultural factors. The findings indicate that workplace justice enhances individual capabilities and community well-being, while politically flexible organizations enhance institutional effectiveness and community participation in democracy and work commitment. Local cultural norms, such as reciprocity, foster solidarity and community engagement. The implications for public administration examine how institutional design, organizational culture, and global citizenship values play a key role in development success.